Études TransInterroger les conditions de production et de diffusion des savoirs - Karine Espineira; Maud-Yeuse Thomas (Genre, Sexualité et Société)
Transgender Studies emerged in the United States in the 1990s, based on one observation: the studies on trans people were in many cases questionable, therefore it seemed necessary to produce situated knowledges (Haraway, 1988). In the Francophone context, these studies suffer from a deficit of recognition and the distinction between studies on transidentity and trans studies is becoming all the more important. Do studies allow so-called or perceived minority knowledge to mark a transition from being an object of knowledge to being a subject of knowledge? Could the recognition of trans studies enable universities and associations to theorize the transgender paradigm on the same basis as their colleagues in the United States, provided that studies on trans and trans studies are not confused? Is assimilation or confusion likely to produce a gentrification of minds (Schulman, 2018) and the subordination of the trans studies to the benefit of the studies on trans?